Internet banking adoption: the level of customer acceptance at Scope International / Mohd Aslam Mohd Ariffin - Mohd Ariffin, Mohd Aslam (Faculty of Business and Management, 2010)
The Internet banking has developed tremendously over the past years and will continue to develop as financial institutions continue to make every effort to allow its customers to complete fund transfers, pay bills and access important information online. As the Internet banking grown significantly, at the same time, it also has been overwhelmed by Internet criminals and fraudsters attempting to steal customer information and money. As a result, the services of Internet banking have become a crucial concern of financial institutions globally. This research examines the factors that determine consumers’ intention to Internet banking at Scope International. Perceived of usefulness is considered to be elementary in determining the acceptance besides security and privacy, legal issues and also trust issues.